Automation of Water Circulation Regulation and Nutritional Administration in Catfish Cultivation Ponds with Bioflocculation Technology - Ashari, Irvan; Yudhana, Anton (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
Many catfish cultivators in Indonesia have failed due to lack of attention to the quality of the water used in aquaculture ponds. Water quality is very influential on the catfish farming system with biofloc technology, water has the most important role for the survival of catfish. This research periodically measures the level of turbidity and pH in the water, then the readings from the sensor will be processed by Arduino Uno which will be displayed on the LCD. In addition, this tool can also schedule the provision of nutrients as desired and is able to perform automatic water changes according to the conditions of the aquaculture pond, if the pH and turbidity conditions of the pond exceed the existing threshold, it will activate the drain pump and water increase. The accuracy of the acidity (pH) sensor has an accuracy rate of 96.21% which is very good, with a standard deviation of 2.49. The turbidity sensor has a standard deviation of 0.133. So this tool is designed to make it easier for cultivators to take care of the pond. The hope is that by making this tool it can overcome or overcome the mortality rate of catfish among cultivators.